Distribuição Binomial e Aplicações - ROCHA, Samy Marques (2017)
The Binomial probability distribution is one of the most commonly used to represent data of discrete random variables. In this work, we present the construction of the Binomial model and its main characteristics. The relationship with other distributions is explored following the theoretical aspects and examples of applications. The examples using data from the Brazilian soccer championship can become a motivational proposal for the students of the High School. The methodology is applied with the computational support of free software Geogebra.